2021
DOI: 10.1371/journal.pcbi.1008398
|View full text |Cite
|
Sign up to set email alerts
|

Numerical evaluation reveals the effect of branching morphology on vessel transport properties during angiogenesis

Abstract: Blood flow governs transport of oxygen and nutrients into tissues. Hypoxic tissues secrete VEGFs to promote angiogenesis during development and in tissue homeostasis. In contrast, tumors enhance pathologic angiogenesis during growth and metastasis, suggesting suppression of tumor angiogenesis could limit tumor growth. In line with these observations, various factors have been identified to control vessel formation in the last decades. However, their impact on the vascular transport properties of oxygen remain … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…In previous literature, the complexity of vascular networks has been typically quantified in terms of the average global characteristics such as the area fraction of the vessels 48 , lacunarity 17 or the so-called branching index, i.e., the linear density of branching points along the vessels 48 . Here, we additionally focus on local morphological features of a branching network, that is on the distribution of the bifurcation angles ϕ .…”
Section: Resultsmentioning
confidence: 99%
“…In previous literature, the complexity of vascular networks has been typically quantified in terms of the average global characteristics such as the area fraction of the vessels 48 , lacunarity 17 or the so-called branching index, i.e., the linear density of branching points along the vessels 48 . Here, we additionally focus on local morphological features of a branching network, that is on the distribution of the bifurcation angles ϕ .…”
Section: Resultsmentioning
confidence: 99%
“…Angiogenic vascular growth is important to improve tissue hypoxia. To investigate whether vessel pruning contributes to the increase of blood flow at the angiogenic front, 3D vascular structures were reconstructed from 2D confocal images using an antibody against ICAM-II, the marker for the endothelial luminal surface as previously established (Mirzapour-Shafiyi et al , 2021). Regressing ECs integrate into neighboring vessels and leave empty sleeves with the EC basement membrane, including collagen type IV as a remnant of the existed vascular connection(Adams & Alitalo, 2007; Baeyens et al , 2016; Baluk et al , 2003; Gerhardt et al , 2003; Potente et al , 2011).…”
Section: Resultsmentioning
confidence: 99%
“… 32 Others have shown that flow speed in the murine retina is affected by vascular branching morphology. 33 Whether the geometrical arrangement observed in capillary vortices and changes in blood viscosity secondary to oral contraceptives or viral infections impact oxygen delivery in the DCP has not yet been addressed. 34 , 35 We believe that this topic should be further studied, as it is likely to expand our understanding of the mechanisms involved in some AMN cases.…”
Section: Discussionmentioning
confidence: 99%